Allogeneic stem cell transplantation in multiple myeloma: is there still a place? - Liberatore, Carmine; Fioritoni, Francesca; Di Ianni, Mauro (Frontiers in Oncology, 2024)
The introduction of novel agents dramatically improved response and outcomes of multiple myeloma (MM) and led to a sharp decline in the use of allogeneic hematopoietic stem-cell transplantation (allo-HSCT). Thus, recent guidelines do not recommend anymore allo-HSCT as consolidation in the firstline treatment of newly diagnosed MM, even in high-risk patients. In relapsed/refractory setting, allo-HSCT is not routinely recommended but should only be performed within clinical trials in young and high-risk patients. Nonetheless, allo-HSCT still represents a potential curative approach that has been used for decades in the treatment of MM and plasma cell neoplasms with favorable results and may still represent a treatment option for carefully selected patients. Despite promising results were obtained with CAR T cell therapies and bispecific antibodies in triple-and penta-exposed/refractory MM, these patients will inevitably relapse. To date, less is known about outcomes of allo-HSCT in patients exposed to novel immunotherapeutic drugs. Therefore, allo-HSCT could represent a reasonable treatment choice for younger and high-risk patients who have relapsed after CAR T cell therapies and bispecific antibodies as well as an alternative for patients not eligible to these treatments and in those countries where immunotherapies are not yet available. In the choice of conditioning, reduced intensity conditioning regimens are currently recommended for the lower toxicity and mortality. Moreover, the use of alternative donors, particularly haploidentical, has progressively increased in last years with results comparable to full matched donors. Finally, post-transplantation maintenance strategies are encouraged whenever feasible.